2021
DOI: 10.1111/hequ.12345
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating theoretical and empirical approaches to employability in different global regions

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…Employability is largely regarded as a measurable economic achievement of graduates and universities. This not only highlights the importance of graduates as key contributors to economic development, but also highlights the role of higher education in promoting the training of graduates for the labor market (Fakunle and Higson, 2021). It has become a common practice to embed employability at the core of the excellent teaching framework (Department for Business, 2016).…”
Section: Employabilitymentioning
confidence: 99%
“…Employability is largely regarded as a measurable economic achievement of graduates and universities. This not only highlights the importance of graduates as key contributors to economic development, but also highlights the role of higher education in promoting the training of graduates for the labor market (Fakunle and Higson, 2021). It has become a common practice to embed employability at the core of the excellent teaching framework (Department for Business, 2016).…”
Section: Employabilitymentioning
confidence: 99%
“…This includes both skills and attitudes. Policymakers' responses to industry requirements and outside circumstances, such as labor market conditions, in relation to graduates' readiness (Fakunle & Higson, 2021). "Conflict theory of employability takes into consideration the fact that society is characterized by inequalities in wealth, power, as well as status, and that these inequalities create conflict between individuals and social groups" (Matsepe, 2002, as cited in Jonck & Walt, 2015).…”
Section: Related Theories On Employabilitymentioning
confidence: 99%
“…"The process approach is considering the employability strategy at the institutional level. The employability initiatives that are available inside an institution are covered by the process approach and these programs include these objectives either expressively or implicitly through the careers service" (Fakunle & Higson, 2021). The human development theory considers employability from the aspect of supply side and focuses on a variety of skills including but not limited to knowledge generation, professional preparation, cultural knowledge, and the enlightenment of the public sphere (Jonck, 2014).…”
Section: Related Theories On Employabilitymentioning
confidence: 99%
“…Employability studies should, therefore, consider the contextual environment of the local labour market. Fakunle and Higson (2021) have highlighted the importance of studies on employability in "non-Western contexts, an area that remains under-researched" (p. 8). Lam and Tang (2021) observed that most of the published work on graduate employment outcomes "do not tell us much about the contextualised processes that 'match' or 'mismatch' graduates' qualifications with 'appropriate' graduate jobs" (p. 14).…”
Section: Significance Of the Studymentioning
confidence: 99%